Efficacy of three novel drugs in the treatment of heart failure: A network meta-analysis. Issue 29 (22nd July 2022) - Luo, Lin; Yang, Xu; Tang, Kai; Wu, Jianli; Li, Dejin; Ran, Jiuju; Zhang, Li; Wang, Dan; Zhao, Dan; Yu, Min; Chen, Anfang; Saranathan, Maya
Abstract : Background: Angiotensin receptor neprilysin inhibitors (ARNI), sodium-glucose cotransporter 2 inhibitors (SGLT2i), soluble guanylate cyclase stimulators (sGCs), and the traditional golden triangle standard-of-care (SOC) are effective drugs for heart failure. We aimed to assess the efficacy of 4 interventions in these patients. Methods: PubMed, The Cochrane Library, Embase, and Web of Science databases were electronically searched to collect randomized controlled trials of 3 novel drugs in the treatment of heart failure from inception to September 1st, 2021. Two reviewers independently screened literature, extracted data, and assessed the risk bias of included studies. Stata 16.0 software was used for network meta-analysis. Results: A total of 17 randomized controlled trial involving 38, 088 patients were included. The results of network meta-analysis: in terms of heart failure rehospitalization rate, 3 novel drugs lower than SOC [ARNI (OR = 0.77, 95% CI: 0.71–0.83), SGLT2i (OR = 0.70, 95% CI: 0.63–0.77), sGCs (OR = 0.88, 95% CI: 0.78–0.99)], and SGLT2i was also lower than sGCs (OR = 0.79, 95% CI: 0.68–0.93). In terms of all-cause mortality, ARNI was lower than SOC (OR = 0.81, 95% CI: 0.66–0.99). In terms of cardiovascular mortality, ARNI and SGLT2i was lower than SOC (ARNI [OR = 0.80, 95% CI: 0.70–0.92], SGLT2i [OR = 0.87, 95% CI: 0.76–0.99]). In terms of rates of cardiovascular death or heart failure rehospitalization, 3 novel drugs lower than SOC (ARNI [OR = 0.76, 95% CI: 0.71–0.82], SGLT2i [OR = 0.76, 95% CI: 0.70–0.82], sGCs [OR = 0.87, 95% CI: 0.78–0.97]). In terms of Kansas city cardiomyopathy questionnaire score, ARNI and SGLT2i was superior to SOC (ARNI [MD = 1.43, 95% CI: 0.43–2.42], SGLT2i [MD = 1.88, 95% CI: 1.12–2.65]). In terms of N-terminal pro-B-type natriuretic peptide outcome indexes, SGLT2i was superior to SOC (MD = −134.63, 95% CI: −237.70 to −31.56). The results of Surface under the cumulative ranking sequencing: in terms of heart failure rehospitalization rate and rates of cardiovascular death or heart failure rehospitalization, the ranking was SGLT2i>ARNI>sGCs>SOC. in terms of all-cause mortality and cardiovascular mortality, the ranking was ARN>SGLT2i>sGCs>SOC. in terms of Kansas city cardiomyopathy questionnaire score and N-terminal pro-B-type natriuretic peptide outcome indexes, the ranking was SGLT2i>ARN>SOC. Conclusions: The available evidence suggests that all 3 novel heart failure drugs can improve the prognosis of heart failure. ARNI may be the most effective in reducing mortality, SGLT2i may be the most effective in improving quality of life, while sGCs may be inferior to ARNI and SGLT2i.